2021
DOI: 10.1134/s1075700721050130
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change as a Factor in the Development of Companies: Corporate Strategies and Guidelines for State Industrial Policy

Abstract: In recent years, the problem of global climate change has become one of the significant challenges for ensuring the sustainability of the functioning and growth in the market value of the world's leading industrial companies. Based on the latest data, the article describes the scale and impact of climate change on the development of companies and also considers some corporate strategies for reducing climate risks and adapting to the consequences of climate change. It is shown that, acting as a significant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many companies have also set their own mid-to long-term sustainability and climate goals. The targets relate to both direct greenhouse gas emissions generated from sources under the company's control and indirect "energy" emissions resulting from consuming purchased electrical and thermal power [11].…”
Section: Corporate Management Specifics In the Sphere Of Climate Chan...mentioning
confidence: 99%
“…Many companies have also set their own mid-to long-term sustainability and climate goals. The targets relate to both direct greenhouse gas emissions generated from sources under the company's control and indirect "energy" emissions resulting from consuming purchased electrical and thermal power [11].…”
Section: Corporate Management Specifics In the Sphere Of Climate Chan...mentioning
confidence: 99%
“…Humanity is facing the consequences of a rapid and unregulated industrial evolution, as indicated by various studies [16] , [17] , [18] . The accelerated anthropogenic impact on the climate, commonly referred to as climate change, has heightened the variability of various climate phenomena, a variety of climatic and environmental factors are considered in the spread and control of vector-borne diseases.…”
Section: Introductionmentioning
confidence: 99%